Experimental Investigation Study on Flexural Behaviour of Basalt Fiber Reinforced Concrete Beam with Steel Fibers - Hareesh, P; Pravin Kumar, S (International Journal of Computer Sciences and Engineering, 2025)
Basalt Fiber-Reinforced Polymer (BFRP) bars are rising as an important choice as inside reinforcement for concrete structures, especially when erosion protection or electromagnetic straightforwardness is looked for. BFRP has been effectively utilizing as a part of the fortifying of the segments and beams. It additionally been executed as reinforcement in the beam and got the satisfactory flexural quality which is progressively the steel Basalt composite bars are made by using basalt filaments and a pitch epoxy folio. They are non-destructive, comprise of 80% strands and have a tensile quality three times that of the steel bar typically utilized as a part of building development. Wherever consumption issues exist, basalt fiber composite bars can possibly supplant steel in reinforced concrete. Contrasted with FRP bar as they are utilized for little sum in building industry the basalt bar are less expensive and have better strength under extraordinary conditions. It is presumed that basalt bars are of awesome enthusiasm for the building business and can be utilized for instance in connect decks, seaward structure and in component structures.